Rapid eye movement sleep does not seem to unbind memories from their emotional context. (22nd June 2013) - Deliens, Gaétane; Neu, Daniel; Peigneux, Philippe
Summary Sleep unbinds memories from their emotional learning context, protecting them from emotional interference due to a change of mood between learning and recall. According to the 'sleep to forget and sleep to remember' model, emotional unbinding takes place during rapid eye movement sleep. To test this hypothesis, we investigated emotional contextual interference effects after early versus late post‐learning sleep periods, in which slow wave and rapid eye movement sleep, respectively, predominate. Participants learned a list of neutral word pairs after induction of a happy or a sad mood, then slept immediately afterwards for 3 h of early or late sleep under polysomnographic recording, in a within‐subject counterbalanced design. They slept for 3 h before learning in the late sleep condition. Polysomnographic data confirmed more rapid eye movement sleep in the late than in the early sleep condition. After awakening, half the list was recalled after induction of a similar mood than during the encoding session (non‐interference condition), and the other half of the list was recalled after induction of a different mood (interference condition). The results disclosed an emotional interference effect on recall both in the early and late sleep conditions, which does not corroborate the hypothesis of a rapid eye movement sleep‐related protection of recent memories from emotional contextual interference. Alternatively, the contextual demodulation process initiated during the first post‐learning night might need several consecutive nights of sleep to be achieved.